23 Barriers and facilitators to adopting choosing wisely recommendations in physiotherapy. (20th August 2018) - Zadro, Joshua; Maher, Christopher; Dodd, Rachael
Abstract : Objectives: The aim of this study is to explore physiotherapist's attitudes, views, and beliefs towards adopting the Australian Physiotherapy Association (APA) Choosing Wisely recommendations. Method: We will conduct a qualitative study using semi-structured interviews; recruiting 25 registered physiotherapist members of the APA (unless data saturation occurs earlier). The APA will help us purposively recruit participants with different clinical backgrounds and levels of experience as they have access to all members' email addresses and data on demographics, years of clinical experience, and practice setting. An interview guide will be developed following a content analysis of ~300 surveys, previously completed by APA members, regarding their views on the Choosing Wisely recommendations. Interview questions will likely explore the barriers and facilitators to adopting Choosing Wisely recommendations. Interviews will be conducted face-to-face or via telephone, lasting ~60 min. Interview data will be analysed using Framework analysis and will involve transcribing the interview from audio-recordings, identifying codes that could be linked by related concepts, grouping concepts into themes, and charting and mapping until the final themes emerge. Results: This study will be designed and reported according to the Consolidated Criteria for Reporting Qualitative Research (COREQ). We anticipate to be in the middle of data collection at the time of the conference but are confident we will have some preliminary data to present. Conclusions: Increasing adoption of the APA Choosing Wisely recommendations is important as the provision of low-value physiotherapy – physiotherapy that provides little-to-no benefit or causes harm, and diverts resources from high-value care – is high. Less than half of physiotherapists use guidelines in practice, and nearly 75% are willing to perform an unnecessary test if requested by a patient. This study will inform on the barriers and facilitators to reducing low-value physiotherapy and will have important implications for refining Choosing Wisely recommendations. Physiotherapists commonly treat people with musculoskeletal conditions (the leading cause of global disability) so replacing low-value physiotherapy with high-value physiotherapy could substantially reduce the enormous global burden of these conditions. The findings from this study will also be relevant to the hundreds of health disciplines worldwide that seek a better understanding of the barriers and facilitators to adopting Choosing Wisely recommendations.